2018
DOI: 10.1093/biolre/ioy261
|View full text |Cite
|
Sign up to set email alerts
|

Intra-amniotic inflammation induces preterm birth by activating the NLRP3 inflammasome†

Abstract: Intra-amniotic inflammation is strongly associated with spontaneous preterm labor and birth, the leading cause of perinatal mortality and morbidity worldwide. Previous studies have suggested a role for the NLRP3 (NLR family pyrin domain-containing protein 3) inflammasome in the mechanisms that lead to preterm labor and birth. However, a causal link between the NLRP3 inflammasome and preterm labor/birth induced by intra-amniotic inflammation has not been established. Herein, using an animal model of lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 181 publications
(247 reference statements)
4
70
0
Order By: Relevance
“…In a nonprimate rhesus macaques chorioamnionitis model induced by intra-amniotic injection of LPS, the amnion upregulated neutrophil accumulation via the chemoattractant IL-8 in an IL-1-dependent manner (169). In a mouse model of intra-amniotic inflammation-induced preterm birth, the NLRP3 inflammasome was activated following IL-1β secretion in the fetal membranes and decidua basalis (170). In addition, IL-1β blockade decreased inflammation-induced preterm labor in mice (171).…”
Section: Other Pregnancy Complications Associated With the Nlrp3 Inflmentioning
confidence: 99%
“…In a nonprimate rhesus macaques chorioamnionitis model induced by intra-amniotic injection of LPS, the amnion upregulated neutrophil accumulation via the chemoattractant IL-8 in an IL-1-dependent manner (169). In a mouse model of intra-amniotic inflammation-induced preterm birth, the NLRP3 inflammasome was activated following IL-1β secretion in the fetal membranes and decidua basalis (170). In addition, IL-1β blockade decreased inflammation-induced preterm labor in mice (171).…”
Section: Other Pregnancy Complications Associated With the Nlrp3 Inflmentioning
confidence: 99%
“…The mechanisms that lead to sterile intra-amniotic inflammation in preterm [46][47][48][49][50] and term [46,[51][52][53][54] labor implicate inflammasomes, which are cytoplasmic high-molecular-weight multisubunit protein complexes that upon assembly induce the activation of caspase-1 [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and the consequent release of mature IL-1β and/or IL-18 [74][75][76][77][78][79][80][81][82]. Accordingly, alarmins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An in vivo study showed that IL-1β mRNA expression is increased in mouse fetal membranes following LPS stimulation (45). Interleukin 1β transcript expression is also increased in term human fetal membranes explants treated with LPS (95).…”
Section: Discussionmentioning
confidence: 99%